Dietary mannose supplementation in phosphomannomutase 2 deficiency (PMM2-CDG) - Roman Taday; Marianne Grüneberg; Ingrid DuChesne; Janine Reunert; Thorsten Marquardt (Orphanet Journal of Rare Diseases, 2020)
Abstract Background PMM2-CDG (CDG-Ia) is the most frequent N-glycosylation disorder. While supplying mannose to PMM2-deficient fibroblasts corrects the altered N-glycosylation in vitro, short term therapeutic approaches with mannose supplementation in PMM2-CDG patients have been unsuccessful. Mannose found no further mention in the design of a potential therapy for PMM2-CDG in the past years, as it applies to be ineffective. This retrospective study analyzes the first long term mannose supplementation in 20 PMM2-CDG patients. Mannose was given at a total of 1–2 g mannose/kg b.w./d divided into 5 single doses over a mean time of 57,75 ± 25,85 months. Protein glycosylation, blood mannose concentration and clinical presentation were monitored in everyday clinical practice. Results After a mean time period of more than 1 year the majority of patients showed significant improvements in protein glycosylation. Conclusion Dietary mannose supplementation shows biological effects in PMM2-CDG patients improving glycosylation in the majority of patients. A double-blind randomized study is needed to examine the role of mannose in the design of a therapy for children with PMM2-CDG in more detail.